Remodelling of Ca2+transport in cancer: how it contributes to cancer hallmarks? - Natalia Prevarskaya; Halima Ouadid‐Ahidouch; Roman Skryma; Yaroslav Shuba (2014)
Cancer involves defects in the mechanisms underlying cell proliferation, death and migration. Calcium ions are central to these phenomena, serving as major signalling agents with spatial localization, magnitude and temporal characteristics of calcium signals ultimately determining cell's fate. Cellular Ca(2+) signalling is determined by the concerted action of a molecular Ca(2+)-handling toolkit which includes: active energy-dependent Ca(2+) transporters, Ca(2+)-permeable ion channels, Ca(2+)-binding and storage proteins, Ca(2+)-dependent effectors. In cancer, because of mutations, aberrant expression, regulation and/or subcellular targeting of Ca(2+)-handling/transport protein(s) normal relationships among extracellular, cytosolic, endoplasmic reticulum and mitochondrial Ca(2+) concentrations or spatio-temporal patterns of Ca(2+) signalling become distorted. This causes deregulation of Ca(2+)-dependent effectors that control signalling pathways determining cell's behaviour in a way to promote pathophysiological cancer hallmarks such as enhanced proliferation, survival and invasion. Despite the progress in our understanding of Ca(2+) homeostasis remodelling in cancer cells as well as in identification of the key Ca(2+)-transport molecules promoting certain malignant phenotypes, there is still a lot of work to be done to transform fundamental findings and concepts into new Ca(2+) transport-targeting tools for cancer diagnosis and treatment.